Cordycepin Inhibits Triple-Negative Breast Cancer Cell Migration and Invasion by Regulating EMT-TFs SLUG, TWIST1, SNAIL1, and ZEB1 - Wei, Chunli; Khan, Md. Asaduzzaman; Du, Jiaman; Cheng, Jingliang; Tania, Mousumi; Leung, Elaine Lai-Han; Fu, Junjiang (Frontiers in Oncology, 2022)
Cancer metastasis is the most important cause of cancer-related death, and epithelial-to-mesenchymal transition (EMT) plays crucial roles in cancer metastasis. Cordycepin (CD) is highly enriched in the medicinally used Cordyceps mushroom. In this study, we conducted the antimetastatic activities of CD, specifically focusing on its regulatory effects on EMT-inducing transcription factors (EMT-TFs) in triple-negative breast cancer (TNBC). Our study showed CD to inhibit the growth, migration, and invasion of BT549 and 4T1 cancer cell lines, by employing cell viability assay and real-time cell analyses. The protein levels of N-Cadherin and E-Cadherin, as well as their transcription factors TWIST1, SLUG, SNAIL1, and ZEB1 in BT549 and 4T1 cells, were estimated by Western blot assays. Results from dual-luciferase reporter assays demonstrated that CD is capable of inactivating the EMT signaling pathway by inhibiting TWIST1 and SLUG expression. Furthermore, in vivo studies with mice carrying cancer cell-derived allograft tumors showed the inhibitory effect of CD on cancer cell growth and metastasis. Furthermore, the additive/synergistic anti-metastasis effect of CD and thymoquinone (TQ), another natural product with promising anticancer roles, was demonstrated by combinational treatment. The results from this research indicate that CD would be a promising therapeutic molecule against TNBC by targeting EMT-TFs, possibly in SLUG, TWIST1, SNAIL1, and ZEB1.